2013
DOI: 10.1002/lary.24357
|View full text |Cite
|
Sign up to set email alerts
|

Grade as a prognostic factor in oral squamous cell carcinoma: A population‐based analysis of the data

Abstract: There is a strong association between histologic grade and survival in patients with AJCC stage I or II oral cavity SCC. High histologic grade in early stage oral cavity cancer is associated with poorer survival and carries independent prognostic value in addition to tumor size, node status, and presence of distant metastasis (TNM) stage. Thus, histologic grade should be considered clinically when making treatment decisions, and multivariable models of survival should include grade as a covariate to improve pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
(63 reference statements)
1
50
0
Order By: Relevance
“…To our knowledge, there is no report of grade as a prognostic factor in tumors of the lacrimal gland; however, our finding that welldifferentiated and moderately differentiated tumors have better survival outcomes is consistent with findings in other head and neck malignant neoplasms. 28,32,34,35 Univariate analysis performed on ACC and SCC again revealed that surgical management improved OS and DSS in SCC and OS alone in ACC. Surgical resection with wide local excision is the mainstay of treatment of tumors of the lacrimal gland.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, there is no report of grade as a prognostic factor in tumors of the lacrimal gland; however, our finding that welldifferentiated and moderately differentiated tumors have better survival outcomes is consistent with findings in other head and neck malignant neoplasms. 28,32,34,35 Univariate analysis performed on ACC and SCC again revealed that surgical management improved OS and DSS in SCC and OS alone in ACC. Surgical resection with wide local excision is the mainstay of treatment of tumors of the lacrimal gland.…”
Section: Discussionmentioning
confidence: 96%
“…Tumor cell proliferation rate is reported as a prognostic factor in head and neck carcinomas (25). In oral cavity epidermoid carcinomas, Ki-67 expression serves as an independent prognostic factor for survival (26).…”
Section: Discussionmentioning
confidence: 99%
“…2,13,25 Tumor differentiation has also been directly associated with overall survival in head and neck cancers, [26][27][28][29] as evident in Figure 2. 2,13,25 Tumor differentiation has also been directly associated with overall survival in head and neck cancers, [26][27][28][29] as evident in Figure 2.…”
Section: Tumor Differentiation a Strong Predictor Of Occult Nodal mentioning
confidence: 97%